Comparison between Serology and PCR Methods for the Diagnosis of Visceral Leishmaniasis - A Moshfe; Z Zarei; B Akhoundi; GH Edrissian; B Kazemi; SH Jamshidi; M Mahmoudi; M Bandehpour; M Mohebali (Armaghane Danesh Bimonthly Journal, 2009)
ABSTRACT: